Keanekaragaman Tumbuhan Paku (Pteridophyta) di Kawasan Candi Gedong Songo Kabupaten Semarang - Saputro, Rizky Wahyu; Utami, Sri (Bioma : Berkala Ilmiah Biologi, 2020)
Gedong Songo Temple Region is one of tourism destination place in Semarang District that has high biodiversity, especially fern plants (Pteridophytes) species diversity. This study aims to determine the species diversity, species abundance, and environmental factor in the Gedong Songo Temple Region. The procedure of collecting fern sample was used cruise method by tracking from entrance to exit.Every kind of ferns species were obtained, the name of species was labeled, and total individuals of every species were counted. Every ferns species were identified and collected as herbarium. The result recorded 18 species that categorized as 11 families. Abundant ferns species are Gleichenia linearis, Histiopteris incisa, Lycopodium cernuum, dan Nephrolepis sp. Environmental factors in the Gedong Songo Temple are temperature has range 22Â°C - 27Â°C, humidity has range 58% - 74%, soil pH has range 6,8 - 7,2, and altitude has range 1.325 m - 1.396 m.